Greek Tragedy, European Odyssey The Politics and Economics of the Eurozone Crisis - Godby, Robert W. (Verlag Barbara Budrich, 2016)
Debate among politicians and academics alike vacillates as to whether the euro is the crowning achievement of a half-century of European integration efforts, or now constitutes a force that threatens to drive European Union member states apart. This book introduces both the political and economic forces at play in the eurozone crisis that have shaped this debate and changed the face of European integration.